2017
DOI: 10.1097/ncq.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Nurse-Managed Telemetry Discontinuation Protocol on Monitoring Duration, Alarm Frequency, and Adverse Patient Events

Abstract: Telemetry monitoring is a limited resource. This quality improvement project describes a nurse-managed telemetry discontinuation protocol aimed at stopping telemetry monitoring when it is no longer indicated. After implementing the protocol, data were collected for 6 months and compared with a preintervention time frame. There was a mean decrease in telemetry monitor usage and a decreased likelihood of remaining on a telemetry monitor until discharge. A nurse-managed telemetry discontinuation protocol was effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
2
10
1
Order By: Relevance
“…Alarm fatigue has a large impact on nurses and their daily workflow. Researchers have shown that there is improved nurse and patient satisfaction with education of nurses regarding alarm safety (Perrin et al, 2017). In providing clinical interventions for management of alarm fatigue, research shows a minimization of nuisance and false alarms (Sendelbach et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alarm fatigue has a large impact on nurses and their daily workflow. Researchers have shown that there is improved nurse and patient satisfaction with education of nurses regarding alarm safety (Perrin et al, 2017). In providing clinical interventions for management of alarm fatigue, research shows a minimization of nuisance and false alarms (Sendelbach et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Benjamin et al (2013), also estimated that with a 35% rate of non-indicated telemetry days there is an excess cost of $ 250,000 per year. Perrin et al (2017), completed a quality improvement project utilizing a nurse driven telemetry monitoring discontinuation protocol. The pre-post study was completed on a 15-bed medical care unit in a hospital.…”
Section: Impacts Of Over-monitoring On Alarm Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…The current literature predominantly uses stand‐alone educational interventions rather than system or workflow changes, and thus the impact may not be sustained. In addition, few studies have examined the impact of nursing‐driven initiatives to limit telemetry use 18 …”
Section: Introductionmentioning
confidence: 99%
“…To this end, one institution moved to ensure that monitoring of all low-risk patients was discontinued in a timely manner, 12 and another institution implemented a nurse-managed monitor discontinuation process in an inpatient unit. 13 A subset of premature ventricular contraction alarms were disabled in one institution after studies showed that these alarms contribute a large amount of the noise load experienced in an inpatient unit, despite being largely non-actionable. 14 The sound of an alarm is often configured to reflect the acuity of the event, so efforts have been taken to reconfigure the acuity of each alarm type, ensuring that only the most serious events will trigger a high-acuity alarm sound.…”
Section: Introductionmentioning
confidence: 99%